2003
DOI: 10.2165/00003495-200363240-00002
|View full text |Cite
|
Sign up to set email alerts
|

What is the Role of NSAIDs in Pre-emptive Analgesia?

Abstract: NSAIDs inhibit the cyclo-oxygenase enzymes, and decrease peripheral and central prostaglandin production. In addition to reducing the inflammation that accompanies tissue injury, decreasing prostaglandin production attenuates the response of the peripheral and central components of the nervous system to noxious stimuli. Such a reduction in the response to pain can reduce the peripheral and central sensitisation induced by noxious stimuli, and reduce the pain experienced in response to subsequent noxious stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
67
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 89 publications
0
67
0
8
Order By: Relevance
“…NSAID decrease prostaglandin production and modify cytokine ratios; as a consequence, NSAID attenuate the nervous system response to noxious stimuli (Ochroch et al, 2003). In accordance with these facts, previous research found that piglets receiving meloxicam preoperatively showed significantly lower cortisol levels 30 min to 4 h after castration than controls (Langhoff et al, 2009), but there was no difference in vocalization during castration in meloxicam-treated and untreated piglets (Reiner et al, 2012).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…NSAID decrease prostaglandin production and modify cytokine ratios; as a consequence, NSAID attenuate the nervous system response to noxious stimuli (Ochroch et al, 2003). In accordance with these facts, previous research found that piglets receiving meloxicam preoperatively showed significantly lower cortisol levels 30 min to 4 h after castration than controls (Langhoff et al, 2009), but there was no difference in vocalization during castration in meloxicam-treated and untreated piglets (Reiner et al, 2012).…”
Section: Discussionmentioning
confidence: 66%
“…Outcomes observed at 24 h after castration may not be accurate indicators for NSAID activity (Ochroch et al, 2003;O'Connor et al, 2014). No effect of treatment on growth was detected; other authors described similar results (Carroll et al, 2006), suggesting that growth rates are not a good indicator of acute pain in piglets.…”
Section: Discussionmentioning
confidence: 90%
“…Nonsteroidal anti-inflammatory drugs produce analgesia and reduce inflammation by inhibiting the enzyme cyclooxygenase and subsequent PG production in the peripheral tissues and central nervous system (Ochroch et al, 2003). Surgery-induced pain consists of 2 phases: an immediate incisional phase and a prolonged inflammatory phase that arises primarily due to tissue damage (Kissin, 2000;Gottschalk and Smith, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…대한 기억을 방해하거나 통증 인지를 저하시키는 것으로 정의된 다 (Kaufman, Epstein, Gorsky, Jackson, & Kadari, 2005;Marret et al, 2005;Norman et al, 2001;Ochroch, Mardini, & Gottschalk, 2003). 몇몇 선행 연구에서 선행진통법이 수술 후 진통제 투여량을 감소시키고 부작용을 완화시키는 것으 로 보고하고 있다 (Grass, 2005;Kim & Yoon, 2006;Marret et al, 2005;White, 2005).…”
Section: 선행진통법은 외과적 자극을 주기 전 제통 요법을 통해 통증에unclassified